Changes in the Fermentation and Bacterial Community by Artificial Saliva pH in RUSITEC System - Guo, Tongqing; Guo, Tao; Cao, Yurong; Guo, Long; Li, Fei; Li, Fadi; Yang, Guo (Frontiers in Nutrition, 2021)
The purpose of the study was to assess artificial saliva (AS) pH on ruminal fermentation and rumen bacteria community in rumen simulation system (Rusitec). The experiment was performed in two treatments (low AS pH vs high AS pH) with four replicates. Low AS pH was sustained by altering composition of the AS (NaHCO3 from 9.8 g/L to 1.96 g/L, Na2HPO4 from 9.3 g/L to 1.86 g/L) according to McDougall’s method. The diets were supplemented with 16 g basic diets with forage to concentrate ratio of 50:50. The experiments was conducted over 13-day incubation periods, with 9 days adaption and 4 days sample collection. Results showed low AS pH decreased dry matter (DM) degradability (64.37 vs. 58.67%), organic matter (OM) degradability (64.38 vs. 59.32%), neutral detergent fiber (NDF) degradability (46.87 vs. 39.94%), acid detergent fiber (ADF) degradability (38.16 vs. 31.13%), and crude protein (CP) degradability (70.33 vs. 62.99%), respectively. Low AS pH increased the proportion of butyrate (P = 0.008) and decreased the proportion of propionate (P < 0.001). At the bacteria community, low AS pH increased the abundances of Spirochaetes (P = 0.001) and Synergistetes (P = 0.004) and decreased the Verrucomicrobia abundance (P = 0.004) in solid-associated bacteria. At the genus level, low AS pH increased the abundance of Lactobacillus (P = 0.050) and decreased the abundance of Schwartzia (P = 0.002) in solid-associated bacteria. The abundances of Prevotellaceae_YAB2003_group (P = 0.040), Schwartzia (P = 0.002) and Ruminobacter (P = 0.043) were lower in low AS pH group compared high AS pH group in liquid-associated bacteria. Low AS pH decreased the number of Ruminococcus albus, Ruminococcus flavefaciens, Fibrobacter succinogenes (P < 0.001) both in solid- and liquid-associated bacteria, respectively. The results of the present study included three groups of bacteria communities according to the different sensitives to rumen pH: the abundances of Lactobacillus, Succinivibrio, Prevotella_7 are increased with decreasing AS pH; the amounts of Ruminococcus albus, Ruminococcus flavefaciens, Fibrobacter succinogenes as well as the abundances of Schwartzia and Ruminobacter decreased with reducing AS pH; the abundances of Selenomonas_1, Rikenellaceae_RC9_gut_group and Succiniclasticum were not affected by AS pH in Rustitec.